PENGARUH KEPUASAN KERJA DAN MOTIVASI KERJA TERHADAP KOMITMEN ORGANISASI PEGAWAI PADA BIDANG PEMBINAAN DAN PEMERIKSAAN DINAS SATUAN POLISI PAMONG PRAJA KABUPATEN BOGOR - Syaiful Anwar; Mujito (Indonesian Journal of Social Science and Education (IJOSSE), 2025)
This study aims to examine the effect of job satisfaction and work motivation on organizational commitment of employees at the Civil Service Police Unit (Satpol PP) of Bogor Regency. The research employed a quantitative causal approach with a population of 65 employees working in the Guidance and Inspection Division of Satpol PP Bogor Regency. Data were analyzed using multiple linear regression. The results revealed that, partially, both job satisfaction and work motivation have a significant effect on organizational commitment, as indicated by the t-value being greater than the t-table. Simultaneously, both variables also showed a significant effect with a P Value of 20.706 and Sig. 0.000 < 0.05. The Adjusted R Square value of 0.381 indicates that job satisfaction and work motivation contribute 38.1% to organizational commitment, while the remaining 61.9% is influenced by other factors not examined in this study. The regression equation obtained is Y = 13.869 + 0.271X1 + 0.449X2, which demonstrates a positive influence of both independent variables on organizational commitment. Among the two variables, work motivation was found to be the most dominant factor, with a regression coefficient of 0.449.